2014
DOI: 10.18869/acadpub.rmm.2.2.45
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Serum Levels of Aluminum and Lead in Dialysis Patients, Pre and post Dialysis

Abstract: Background: Accumulation or deficiency of trace elements can occur in hemodialysis patients and it increases risk of cardiovascular or other organs disorders. Special ions levels such as sodium and bicarbonate in dialysis fluid are accurately regulated but the remaining elements are not regularly measured. Aluminum and lead belong to the biologic performance free heavy metals .They also has a tendency to accumulate in hemodialysis patients. This study aims to compare serum Al and lead levels in hemodialysis pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Therefore, environmental exposure to lead, even at low levels, may increase the BLL in these patients. These results are in agreement with other randomized studies on ESRD patients and blood lead levels [21,22]. However, a study on aluminum and lead in ESRD showed that appropriate dialysis adequacy had no effect on serum metal levels before and after dialysis [22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, environmental exposure to lead, even at low levels, may increase the BLL in these patients. These results are in agreement with other randomized studies on ESRD patients and blood lead levels [21,22]. However, a study on aluminum and lead in ESRD showed that appropriate dialysis adequacy had no effect on serum metal levels before and after dialysis [22].…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with other randomized studies on ESRD patients and blood lead levels [21,22]. However, a study on aluminum and lead in ESRD showed that appropriate dialysis adequacy had no effect on serum metal levels before and after dialysis [22]. Another study in 2011 stated that patients with high blood lead levels have higher Kt/V and urea values that can be attributed to the higher blood flow rate and dialysate flow rate.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, the high levels of Pb we measured in the blood of HD patients should be further investigated, as it is well known that Pb is distributed to the kidneys after gastrointestinal absorption. Atieh Makhlough et al [ 33 ] noted that elevated Pb levels in HD patients could be due to almost complete loss of renal function and difficulty in removing Pb during hemodialysis. The status of serum U in patients on HD is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained for B. subtilis WPI growth within 10 days of incubation indicated that the highest and lowest growth rates on 5 and 10 days were 2.6×10 4 and 0.73×10 4 CFU/mL, respectively ( Figure 1A). Moreover, this bacterium had the best growth rate at 35°C and the highest light absorption at this temperature was 0.35.…”
Section: Optimal Conditions For Bacterial Growthmentioning
confidence: 97%
“…Lead (Pb) as one of the most toxic elements that enter the environment through various industries, such as petrochemicals, battery pro-duction, crystallization, mining, lead processing, and mainly burning of fossil fuels. Lead is a metal without biological function [3,4].…”
Section: Introductionmentioning
confidence: 99%